Women as Commodities: An Analysis of Little Women Adaptations - Sephia Dwinusa Putri (Universitas Muhammadiyah Semarang, 2023)
This study examines the portrayal of women as commodities and their agency in the adaptations of Little Women through the lens of Luce Irigaray's